Understanding and minimising water vapour co-adsorption for activated carbons in post-combustion CO2 capture - Albazzaz, Shaima (2020)
The adsorption properties of activated carbons for post-combustion CO2 capture are affected by water vapour, where co-adsorption can significantly increase the regeneration energy for desorbing CO2. This research aims to understand and minimise water vapour co-adsorption on activated carbons while maintaining a high capacity for CO2, and determining the role of organosiloxane compounds as a coating agent to increase the hydrophobic nature of activated carbons. The activated carbons CS and PR that used in this work were derived separately from coconut shell and phenolic resin. Intercalation of potassium into the carbons was investigated since it is established that this increases CO2 adsorption capacities significantly. The KOH-activated carbons (CSK and PRK) were coated using a range of organosiloxane compounds and heat treatment of coated activated carbon at different temperatures was investigated to try to maximise CO2/H2O selectivity. Heat treatment was used to achieve an acceptable balance between the amount of CO2 adsorbed and the effect of the coating film. At equilibrium, the coated samples gave much lower CO2 adsorption capacities and H2O uptakes compared to the initial KOH-activated carbons due to pore blockage. The two samples, CSKV450 and PRK450, which coated by vinyltrimethoxysilane (VTMOS) and heated to 450 °C exhibited the best results compared to other heat-treated samples, a significant reduction in H2O uptake was observed but the reductions in CO2 adsorption were still evident. A detailed assessment of H2O uptake was performed on the CSKV450 sample using dynamic vapour sorption at 25 °C with different relative humidities (10 %, 50 % and 95 %RH). The results were compared with those obtained from non-calcined samples (CS, CSK, and CSKV). At low RH (10 %) and a short contact time (10 minutes), the CO2/H2O selectivity for CSK was 2.37 compared to only 0.77 for CS. This provides evidence that intercalation of potassium ions increase CO2 adsorption at the expense of H2O. Additionally, the selectivity for CSKV450 (2.12) was close to the selectivity of CSK due to removing most of coating layers after heat treatment. Although the same trend was observed at 50 % and 95 %RH, no significant differences were observed between the samples, and the CO2/H2O selectivity remained low, not exceeding 0.6. At working capacity (75% of the equilibrium capacity of CO2), the H2O uptake of CSKV450 is 4.2 wt%, the regeneration heat (Qreg) is 2.26 GJ/tonne CO2, which is nearly double the regeneration heat in dry conditions, which means, each 1% of moisture led to increase about 0.25 GJ/tonne CO2 of the regeneration heat. Qreg in wet condition is lower than that in different types of aqueous amine solutions ( about 3 GJ/tonne CO2) and PEI/silica (2.46 GJ/tonne CO2 in wet condition 2 wt%).